2019
DOI: 10.18502/ijhoscr.v13i2.690
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of RFLP Haplotypes β- Globin Gene Cluster in Beta-Thalassemia Patients in Central Iran

Abstract: Introduction: Beta-thalassemia is one of the most prevalent inherited blood diseases among Iranians. The aim of this study was to elucidate the chromosomal background of beta-thalassemia mutations in Esfahan province, Iran. Materials and Methods: In this study, we investigated three frequent mutations (c.315+1G>A, c.93-21G>A and c.92+5G>C in β-globin gene, the frequency of RFLP haplotypes, and LD between markers at β-globin gene cluster) in 150 beta-thalassemia patients and 50 healthy individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The results showed that 50% of betathalassemia patients were associated with these mutations. The most common haplotype of this study was observed in 39.33% of patients and 46% of normal individuals [25]. It was identified [26] that 20 different mutations in the beta-globin gene associated with beta-thalassemia disease.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The results showed that 50% of betathalassemia patients were associated with these mutations. The most common haplotype of this study was observed in 39.33% of patients and 46% of normal individuals [25]. It was identified [26] that 20 different mutations in the beta-globin gene associated with beta-thalassemia disease.…”
Section: Discussionmentioning
confidence: 53%
“…It was related [25] that 150 patients with beta-thalassemia and 50 healthy individuals with RFLP polymorphisms were studied. Also, three abundant mutations named c.315G> A, c.93-21G> A, and c.92 + 5G> C were examined.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were screened by five restriction enzymes via restriction fragment length polymorphism (RFLP): Hinc II, Hind III, Hinf I, Ava II, and BamHI [20]. The β-globin gene cluster and the location of the different restriction sites used in the study are shown in Figure 1 [21]. The targeted restriction sites were amplified through polymerase chain reaction (PCR) using mutation-specific primers and procedures [22][23][24].…”
Section: Dna Isolationmentioning
confidence: 99%